1998
DOI: 10.1002/(sici)1097-4628(19981114)70:7<1299::aid-app6>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Molecular origin of unusual physical and mechanical properties in novel phenolic materials based on benzoxazine chemistry

Abstract: ABSTRACT:The effect of temperature on hydrogen bonding was investigated by measuring the integrated infrared absorbance of various hydrogen-bonding modes as a function of temperature. It was found that conformationally preferred hydrogenbonding modes maintain constant intensities over the wide temperature ranges studied for both polybenzoxazines and a novolac-type phenolic resin. In particular, the O---H---N hydrogen bond shows strong bonding that does not change over the temperature range. On the other hand, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
94
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 124 publications
(97 citation statements)
references
References 10 publications
3
94
0
Order By: Relevance
“…Polybenzoxazines exhibit unique properties like nearly zero shrinkage upon curing, good thermal stability, good chemical resistance, low water absorption and wide processing window [7][8][9][10][11] . Though the dielectric constants of polybenzoxazines are low, it needs to be reduced further to find better utility in microelectronics applications.…”
Section: Introductionmentioning
confidence: 99%
“…Polybenzoxazines exhibit unique properties like nearly zero shrinkage upon curing, good thermal stability, good chemical resistance, low water absorption and wide processing window [7][8][9][10][11] . Though the dielectric constants of polybenzoxazines are low, it needs to be reduced further to find better utility in microelectronics applications.…”
Section: Introductionmentioning
confidence: 99%
“…It may be assumed that H-bonds present in the epoxy-benzoxazine blend prevented orientation and arrangement of polyether chains into crystal structure. Intermolecular bonds in the epoxy-benzoxazine system have been demonstrated and studied by several authors [4,15,33,34]. Therefore, from results obtained by DSC measurements it may be concluded that benzoxazine surfactant should be homogeneously incorporated in epoxy matrix and that secondary interactions between epoxy and benzoxazine compounds were established.…”
Section: Curing Behavior Of Epoxy-benzoxazine Filmsmentioning
confidence: 93%
“…3 The intermolecular hydrogen-bonding interactions could be significantly reduced at the elevated temperature (viz. 3 The intermolecular hydrogen-bonding interactions could be significantly reduced at the elevated temperature (viz.…”
Section: Hydrogen-bonding Interactionsmentioning
confidence: 99%
“…[1][2][3][4][5] Different with other thermosetting (TS) resins such as epoxy, cyanate ester, and bismaleimide resins, PBZ has a lot of intramolecular or intermolecular hydrogen bonds (H-bonds) [Scheme 1(a, b)], 6 which endow PBZ with amazing properties, such as high glass transition temperature (T g ), high modulus, and low moisture absorption. [1][2][3][4][5] Different with other thermosetting (TS) resins such as epoxy, cyanate ester, and bismaleimide resins, PBZ has a lot of intramolecular or intermolecular hydrogen bonds (H-bonds) [Scheme 1(a, b)], 6 which endow PBZ with amazing properties, such as high glass transition temperature (T g ), high modulus, and low moisture absorption.…”
Section: Introductionmentioning
confidence: 99%